KUALITAS PENDIDIKAN SEKOLAH INKLUSIF DI SMPN 2 KUNDURAN BLORA, JAWA TENGAH - Faiq Hammam Nur Aufa; Nina Widowati; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
This research aims to explain the Analysis of the Quality of Inclusive Education Services at SMPN 2 Kunduran Blora, Central Java. The provided services are not optimal because there are no supporting facilities for inclusive children, no special assistant teachers, and damaged road conditions. This is qualitative descriptive research. The data are collected using interviews, documentation, and literature reviews. This research uses an accidental technique, snowballing sampling, and service theory to examine and identify some factors that disrupt the implementation of inclusive services at SMPN 2 Kunduran Blora, Central Java. The results show that inclusive services are not yet implemented optimally. It can be seen from the service indicators that include Tangible, Reliable, and Access (ease of accessing communication and location). There are no supporting media for children with disabilities, and the school does not have special assistant teachers. Besides, the roads which lead to SMPN 2 Kunduran are badly damaged. Some factors that disrupt the inclusive services such as no supporting infrastructure for the children with special needs, the teachers do not yet have specific competence to educate the children with special needs, and bad road conditions. The researchers suggest that SMPN 2 Kunduran should conduct a rolling system for the teachers of children with special needs to teach at SMPN 2 Kunduran at least once a week. Special training should also be held for homeroom teachers based on inclusion programs. These recommendations also apply to future researchers who want to study inclusive schools in the Blora regency.